Zakat Kelapa Sawit Antara Ketentuan Syariah dan Praktik Masyarakat: Sebuah Analisis Empiris - Siregar, Rosnani; Arsad Nasution , Muhammad (Liwaul Dakwah: Jurnal Kajian Dakwah dan Masyarakat Islam, 2025)
The oil palm farming community in South Labuhan Batu (LABUESEL) area is included in the category of oil palm farmers whose income reaches the zakat nisab, but the culture of increasing zakat from oil palm harvests has not been realized properly. Meanwhile, oil palm farming has become one of the agricultural commodities that must be zakated based on the verse of the Qur'an, Al-Baqarah 267. The problem that then arises is what are the factors causing the oil palm farming community in LABUSEL to not fully pay zakat from their oil palm farming results. The collection of data to answer this problem was carried out through observation and interviews with oil palm farmers in the Muzakki category. The results of the study showed that there were three factors causing The LABUSEL’s oil palm farming community not to fully pay zakat on their oil palm farming products, namely: understanding of Shafi'i fiqh which provides criteria for agricultural zakat that must be paid only on staple foods, following the habits of the community who still do not pay zakat on oil palm farming, not knowing that oil palm harvests are a taxable commodity according to Islamic law, and not knowing that there is a regional regulation regarding oil palm harvests including commodities that must be paid zakat if they meet the requirements.